Networks and Speed of Internationalization: A Multiple Case Study of Emerging Market IT Firms - Mello, Renado Dourado Cotta de; Barreto, Leonardo Gustavo Pereira; Kogut, Clarice Secches (Internext, 2020)
Objective: This study aims to analyze the internationalization processes of two Brazilian IT firms from the perspective of business networks, seeking to understand the reasons that led these firms to internationalize, the factors influencing the process, and, above all, the importance of business networks. Method: a qualitative approach, based on multiple case study method was chosen. Main results: It was found that, although the firms internationalized for different reasons and in different ways, the propositions of the Network Theory, to a greater or lesser extent, were sufficiently robust to explain the internationalization processes of the two firms. Furthermore, in the case in which relationship networks played a more relevant role, the speed of internationalization was higher. Relevance / Originality: The present study addresses two literature gaps noted by Chetty and Stangl (2010): (i) the study of small and medium-sized enterprises in relation to internationalization, innovation, and networks; and (ii) the qualitative testing of the propositions raised by the authors on these subjects. Contributions: Both managerially – by stressing to managers and entrepreneurs the importance of relationship networks for the internationalization of firms, using real cases – and academically – by contributing to the literature on firm internationalization and network theory (NT).